2022
DOI: 10.3389/fpubh.2022.1038296
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting intervention strategies for mental health of COVID-19 patients: A network analysis based on a survey in Omicron-infected patients

Abstract: BackgroundThe COVID-19 pandemic had a major impact on people's mental health. As the SAS-Cov-2 evolves to become less virulent, the number of asymptomatic patients increases. It remains unclear if the mild symptoms are associated with mild perceived stress and mental illness, and the interventions to improve the mental health of the patients are rarely reported.MethodsThis cross-sectional study investigated the level of depression, anxiety and perceived stress of 1,305 COVID-19 patients who received treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…Considering the relatively mild nature of the Omicron variant [ 28 ], there may have been a smaller biological inflammatory response, leading to a potentially reduced effect on depression and anxiety levels. This is consistent with a previous study conducted on SARS-CoV-2 infected inpatients, where patients with Omicron variant infection exhibited decreased depression and anxiety symptoms [ 29 ]. This suggests a relatively low risk of experiencing depression and anxiety due to Omicron variant infection in community samples.…”
Section: Discussionsupporting
confidence: 92%
“…Considering the relatively mild nature of the Omicron variant [ 28 ], there may have been a smaller biological inflammatory response, leading to a potentially reduced effect on depression and anxiety levels. This is consistent with a previous study conducted on SARS-CoV-2 infected inpatients, where patients with Omicron variant infection exhibited decreased depression and anxiety symptoms [ 29 ]. This suggests a relatively low risk of experiencing depression and anxiety due to Omicron variant infection in community samples.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, our study provides the first network-based analysis of the long-term mental health sequelae of COVID-19 Our study suggested that the most central symptom within the network was uncontrollable worry, which aligned with previous network analyses of depression and anxiety symptoms among other populations during the COVID-19 pandemic (17,33). Similarly, a recent study suggested that uncontrollable worry was one of the core symptoms in the network of depression-anxiety-stress among patients with recent COVID-19 infection (21). A possible explanation for the high centrality of uncontrollable worry in COVID-19 patients might be the COVID-19-related fear, such as reinfection and sequelae.…”
Section: Discussionsupporting
confidence: 87%
“…To date, emerging studies have documented the network structure of mental distress (mainly depression and anxiety) in different populations such as the general population (16), adolescents (17), college students (18), and healthcare workers (19,20) during the COVID-19 pandemic. However, to our knowledge, only two studies assessed the network of mental distress in COVID-19 patients (21,22). Both studies recruited patients with recent infections (patient's 1-month after discharge or patients in the Fangcang shelter hospitals).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because Omicron occurred in the third year of the COVID-19 pandemic, the general population tended to show better resilience to the pressure compared with the early pandemic, as reviewed by Manchia et al [ 47 ]. One study among 1,305 patients positive for Omicron in China also supported this finding, as the prevalence of depression, anxiety and perceived stress in this population was lower than during the early pandemic (9.03, 4.60 and 17.03%, respectively) [ 48 ].…”
Section: Discussionmentioning
confidence: 77%